A MODEL OF MATE GUARDING - Grafen, A; Ridley, M (1983)
Precopulatory mate guarding is the habit, practised by many species, of the two sexes' joining together in intimate pairs for some time, usually days, before mating. It is mainly found in species in which mating is confined to a very short period of the female's reproductive cycle. A mathematical model confirms that precopula will evolve when mating is restricted in time. The model also specifies the evolutionary stable duration of precopula. There are two models: in the simpler, males cannot take over paired females; in the second, larger males can take over females from smaller males. In the model with takeovers, larger males guard for less time than smaller males, and the average guarding duration for all males is shorter than in the model in which there were no takeovers. © 1983.